Student perception and performance using the online tools Socrative® vs. Kahoot!® in the discipline of Urology - Oliveira,André Matos de (2021)
Abstract: Introduction: Active methodologies are tools aimed at engaging students in the learning process. Through them, the student is confronted with problem situations and, to solve them, they need to actively participate in the construction of the solution. Socrative® and Kahoot!® are tools that can be used to support the growing demand for new teaching methods. Objective: This study aims to compare the scores obtained by urology student in pre-tests applied using the Socrative® and Kahoot!® applications, and to analyze the students’ perceptions after the exposure to the learning tools. Method: A prospective and comparative study was carried out on the use of the Socrative® and Kahoot!® applications in the discipline of Urology of the medical course. The cohort consisted of two classes of students, 193 in total. Students were divided into six groups, separated in two different schedules, and they took turns weekly switching the tools. The methodologies were used as a pre-test during the tutorial sessions, aiming to compare the grades obtained by the students between the applications. At the end of the course, the students answered a perception questionnaire in relation to each platform. The data were statistically analyzed using the program SPSS Statistics v.20.0. The Wilcoxon non-parametric test and the Chi-square test were used. Values of p <0.05 indicated statistical significance. Result: The Socrative® application obtained better results in terms of the number of correct answers and in relation to the students’ satisfaction. Among the six topics addressed in the pre-tests, two showed higher scores with the Socrative® tool (p = 0.017 and p = 0.042). As for the perception questionnaire, the Socrative® tool showed an average score 1.8 points higher than Kahoot!® (0 - 10 scale), and statistical significance was found in seven out of the eight evaluated questions. Conclusion: The Socrative® tool showed higher grades and was more satisfactory to students than Kahoot!®.